DuoTube: Inspiring Experimental Creativity in Common Digital Spaces - Ralph Lewis; Robin Meiksins (Journal of the Association for Technology in Music Instruction, 2025)
This paper reflects on the ways an easy to access work for laptop has been of use to ensembles and music educators. It explores experimentalism and electronic music using technology typically found in a computer lab or a home computer and allows for playful exploration in group or solo situations. Near the end of the talk, an excerpt of the work will be demonstrated to help show how it relatively easy to onboard, try out, and ideally try it out at home/school later on.